Detection of the power spectrum of cosmic microwave background lensing by the Atacama Cosmology Telescope. - Das, S; Sherwin, B; Aguirre, P; Appel, J; Bond, JR; Carvalho, C; Devlin, M; Dunkley, J; Dünner, R; Essinger-Hileman, T; Fowler, J; Hajian, A; et al. (2011)
We report the first detection of the gravitational lensing of the cosmic microwave background through a measurement of the four-point correlation function in the temperature maps made by the Atacama Cosmology Telescope. We verify our detection by calculating the levels of potential contaminants and performing a number of null tests. The resulting convergence power spectrum at 2° angular scales measures the amplitude of matter density fluctuations on comoving length scales of around 100 Mpc at redshifts around 0.5 to 3. The measured amplitude of the signal agrees with Lambda cold dark matter cosmology predictions. Since the amplitude of the convergence power spectrum scales as the square of the amplitude of the density fluctuations, the 4σ detection of the lensing signal measures the amplitude of density fluctuations to 12%.